An analysis of spatial distribution characteristics and driving factors of traditional villages in the Loess Plateau - Xiaobin Bao; Yingna Yang; Jianqing Qi; Yanbing He (PLoS ONE, 2025)
By revealing the spatial distribution characteristics and driving mechanisms of 1,027 traditional Chinese villages in the Loess Plateau, as announced in six batches up to 2023, this article provides a theoretical basis for formulating scientific and differentiated protection and development strategies. Utilizing the ArcGIS 10.8 platform and the GeoDetector model, this study comprehensively applies methods including the nearest neighbor index, standard deviation ellipse, kernel density estimation, and spatial autocorrelation to systematically analyze the spatial pattern of traditional villages, and quantitatively reveals their key driving factors and interactions through the GeoDetector. The results show: (1) Traditional villages in the Loess Plateau present a significant clustered spatial distribution (Nearest Neighbor Index R = 0.47, Moran’s I = 0.189), with an overall pattern of “dense in the east and west, sparse in the center,” primarily concentrated within an elliptical area with an flattening ratio of 0.664 and a directional angle of 84.5°, and with high-density areas located in Shanxi Province, the Yellow River basin along the Shanxi-Shaanxi border, and the Hehuang Valley. (2) Spatially, five major core clusters are formed, presenting a layered structure of “core clustering, gradient transition,” and exhibiting a non-stable diffusion trend towards the periphery. (3) The spatial differentiation is a result of the synergistic driving of human and natural factors, with human factors having a stronger overall explanatory power. Among them, the density of cultural heritage sites (q = 0.546) is the primary driving factor, followed by annual precipitation (q = 0.458), population size (q = 0.457), and urbanization rate (q = 0.354). The interaction between factors is significant and mostly shows non-linear enhancement, for instance, the interactive explanatory power of population size and the density of cultural heritage sites is as high as 0.852.